A proposed field test for evaluating fitness in elderly hypertensive patients. - C. J. Eales; A. V. Stewart (South African Journal of Physiotherapy, 1997)
There is a very high incidence of hypertension amongst the black population in South Africa. Regular aerobic exercise has been shown to be an effective method of lowering blood pressure. In order to be able to prescribe exercise for patients in a community-based setting, an easily administered exercise test needs to be used. In this study the 6 minute walking test in conjunction with the Borg scale and the Duke Activity Status Index (DASI) were tested on three groups of hypertensive patients from different socio-economic communities. The mean age of the cohort was 64.1 years (SD+-7.9) and males and females were included. The outcome was evaluated by determining the degrees of agreement between the DASI and the age predicted V02max (-0.3295) as well as between the calculated V02max and the age predicted V02max (-0.3045). The tests were easy to administer and the calculations easily done. The agreement between the 6 minute walking test and the DASI test was clinically acceptable (-0.0250). There was no agreement between the values obtained and the age-predicted values. It was concluded that the walking test is a useful field test for exercise performance